COVID-19 vaccination: public preference and intention in Vietnam - Tran, V. D.; Huynh, T. M. D.; Pham, D. T.; Le, M. H.; Dorofeeva, V. V.; Dewey, R. S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Backgrounds. Understanding public opinion in relation to vaccination is critical, as there are several COVID-19 vaccines approved for use in Vietnam. This study aimed to assess public COVID-19 vaccine preferences and intention in Can Tho, Vietnam.Methods. An analytical cross-sectional study was performed between September 20 and October 20, 2021. in people aged 18 and over living in Can Tho, Vietnam, A questionnaire captured demographic information, vaccination intention, preference for vaccine selection, and barriers and motivations related to COVID-19 vaccination. Predictors for vaccination willingness among unvaccinated people were determined using multivariable logistic regression.Results. Out of the proposed vaccines that have been approved by the Vietnam Ministry of Health, AstraZeneca (31.4%), Pfizer (23.5%), and Moderna (14.7%) were the most preferred by participants. Out of 1,470 respondents, 35.8% have received at least one vaccine dose, and of these, 76.9% intended to continue to receive vaccinations. Among the unvaccinated, 74.8% reported that they would be willing to complete the vaccination. Most participants stated that they would receive a COVID-19 vaccine if provided with adequate information on effectiveness and safety (92.7%). The possibility of side effects after vaccination (75.4%) was the most important barrier to vaccination. Education, health status, and prior flu-vaccination were associated with the intention to receive a COVID-19 vaccination among those who had not previously received one. Conclusions. Many unvaccinated adults were willing to receive a COVID-19 vaccination, with AstraZeneca being the preferred choice. These findings could help in the planning of vaccination campaigns to increase vaccination uptake in Vietnam.